2009
DOI: 10.1021/bi900038p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Binding Kinetics of the Hepatitis C Virus NS3 Protease Inhibitor ITMN-191 Reveals Tight Binding and Slow Dissociative Behavior

Abstract: The protease activity of hepatitis C virus nonstructural protein 3 (NS3) is essential for viral replication. ITMN-191, a macrocyclic inhibitor of the NS3 protease active site, promotes rapid, multilog viral load reductions in chronic HCV patients. Here, ITMN-191 is shown to be a potent inhibitor of NS3 with a two-step binding mechanism. Progress curves are consistent with the formation of an initial collision complex (EI) that isomerizes to a highly stable complex (EI*) from which ITMN-191 dissociates very slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
(93 reference statements)
1
39
0
Order By: Relevance
“…The covalent enzyme-inhibitor complex is usually very stable. Progress curve analysis showed that SCH 900518 dissociates from the stable complex with a half-life of 1 to 2 h, which is similar to that of telaprevir (1 to Ͼ5 h) (16)(17)(18) and slightly shorter than that of boceprevir (10 to 20 h) (12) but significantly longer than that previously reported for BILN 2061 (on the order of minutes) (8,18). Estimates of the value of the dissociation constant can vary by the different types of assays FIG.…”
Section: Discussionmentioning
confidence: 90%
“…The covalent enzyme-inhibitor complex is usually very stable. Progress curve analysis showed that SCH 900518 dissociates from the stable complex with a half-life of 1 to 2 h, which is similar to that of telaprevir (1 to Ͼ5 h) (16)(17)(18) and slightly shorter than that of boceprevir (10 to 20 h) (12) but significantly longer than that previously reported for BILN 2061 (on the order of minutes) (8,18). Estimates of the value of the dissociation constant can vary by the different types of assays FIG.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the single mutant A156T or A156V or the double mutant at positions 36/155 or 36/156, all conferring high-level resistance, were observed in some VX-950-treated patients. Similarly, samples from SCH-503034-treated patients revealed the emergence of the low-to moderate-level resistance mutations T54A, V170A, and A156S and, less commonly, the high-level resistance mutant A156T (27, 28).More recently, other HCV PIs, including , have progressed to the early stages of clinical evaluation (12,15,19,20,23,29). These compounds are structurally related macrocyclic inhibitors that are chemically distinct from VX-950 and SCH-503034.…”
mentioning
confidence: 99%
“…More recently, other HCV PIs, including , have progressed to the early stages of clinical evaluation (12,15,19,20,23,29). These compounds are structurally related macrocyclic inhibitors that are chemically distinct from VX-950 and SCH-503034.…”
mentioning
confidence: 99%
“…Collectively, our data suggest that ITMN-8187 could be developed for use in once-daily treatment regimens in combination with other directly acting antiviral agents. Biochemical inhibition studies (data not shown) indicate that ITMN-8187 associates with genotype 1a and 1b NS3/4A proteases through a slow/tight binding mechanism with slow dissociation (off-rate) similar to that noted previously for danoprevir (26). While the importance of increased drug target residence times to efficacy has been demonstrated in other systems (32), its contribution here is uncertain given the absence of reliable measures of HCV protein turnover and synthesis rates (26).…”
Section: Discussionmentioning
confidence: 67%